Molecular sieve for adsorbing and separating ethylene and ethane as well as preparation method and use method of molecular sieve

By using Ag-Na-LTA molecular sieve with synergistic Ag-Na dual ion as an adsorption material, the problem of poor separation effect of ethylene and ethane in the prior art is solved, and more efficient adsorption selectivity and working adsorption capacity are achieved.

CN119771346APending Publication Date: 2025-04-08NORTHEAST GASOLINEEUM UNIV +1

Patent Information

Application Number
CN202411963863.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When separating ethylene and ethane, the prior art has similar physical and chemical properties, resulting in high energy consumption and poor results in conventional separation technologies, which cannot meet the needs of industrial production and scientific research.

Method used

Ag-Na-LTA molecular sieve with Ag-Na dual ions synergistically acted as an adsorption material, and was prepared through ion exchange and calcination to improve the adsorption selectivity of ethylene.

Benefits of technology

The adsorption selectivity of ethylene is significantly improved, and a new adsorption material is provided, which adds a new optional approach to adsorption separation of ethylene and ethane technology, and has better operating adsorption capacity to ethylene compared with the existing configuration molecular sieve.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771346A_ABST
    Figure CN119771346A_ABST
Patent Text Reader

Abstract

The invention discloses a molecular sieve for adsorbing and separating ethylene and ethane as well as a preparation method and a use method thereof, and belongs to the field of gas adsorption and separation, the molecular sieve is a molecular sieve with LTA configuration, the preparation method comprises the following steps: drying and calcining an ion exchange product of silver salt and LTA molecular sieve, and component cations of the molecular sieve at least comprise Na < + > ions and Ag < + > ions; according to the method, the content of Ag is effectively controlled, the problem that the selectivity of an existing adsorbent for separating C2H4 / C2H6 is not ideal is solved, and a feasible technical route is provided for effective recycling of high-added-value products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a molecular sieve and a preparation method and a use method thereof, and in particular to a molecular sieve for adsorption separation of ethylene and ethane and a preparation method and a use method thereof, belonging to the field of gas adsorption separation. Background Art

[0002] Ethylene and ethane are two common hydrocarbon compounds in oil and gas processing. Ethylene is an important raw material in the chemical industry and is widely used in plastics, rubber, textiles, coatings and chemicals. It can be used to produce various organic compounds, such as polyethylene, ethanol, acetaldehyde, etc. With the development of the chemical industry, the demand for high-purity ethylene and ethane is also increasing. Therefore, ethane dehydrogenation to ethylene technology has huge commercial potential in the global market. Therefore, the background of ethylene and ethane separation technology mainly involves the development of the petroleum industry and the chemical industry, as well as the growing demand for high-purity ethylene and ethane. Since ethylene and ethane have very similar physical and chemical properties, whether boiling point, size, spatial configuration, relative volatility are very similar, the conventional separation technology using the difference in physical properties has high energy consumption and poor effect. Therefore, some other efficient separation technologies need to be developed to improve the separation effect of ethylene and ethane to meet the needs of industrial production and scientific research.

[0003] Currently, cryogenic distillation, membrane separation and adsorption separation are common methods for separating ethylene and ethane, but the former two have various shortcomings for separating ethylene and ethane.

[0004] The cryogenic distillation process is to liquefy the high-pressure raw gas partially or completely through multiple throttling expansions, and then separate the two by distillation according to the difference in relative volatility of ethylene and ethane. The boiling point of ethane is 184.6K, and the boiling point of ethylene is 169.5K. The difference between the boiling points is 15.1K, and low temperature conditions are required to separate ethylene and ethane. The deethanizer system is an important part of the separation process of the ethylene plant, and its operation directly affects the quality and yield of ethylene and propylene products. In the sequential separation process, the feed of the deethanizer is the bottom material of the demethanizer, which is composed of carbon two and carbon two and above fractions. After separation in the deethanizer, the carbon two product at the top of the tower is sent to the carbon two hydrogenation system and the ethylene distillation system to obtain ethylene products. This method is costly and consumes too much energy.

[0005] US20220331709A1 discloses a process for separating ethylene and ethane by cryogenic distillation. The process part uses distillation to separate one or more condensates from the separation input, and the condensates are cryogenically distilled to obtain a gaseous first fraction and a liquid second fraction, wherein the gaseous first fraction contains at least ethylene and ethane, the proportion of which is lower than the proportion in the separation input, and contains compounds with lower boiling points than ethylene and ethane and a higher proportion than the proportion in the separation input.

[0006] The membrane separation process uses a special membrane to separate a mixed gas into different components. In the separation of ethylene and ethane, ethylene and ethane coexist, and sometimes it is necessary to separate pure ethane or ethylene from the mixture. In this process, the ethylene and ethane mixture is first sent to the membrane separation unit. Through the selection of membrane materials and special process conditions, the membrane can selectively allow ethane to pass through and prevent ethylene from passing through. This selectivity is based on the difference in the size and interaction properties of the two molecules. By adjusting parameters such as flow, temperature and pressure, efficient separation can be achieved. Finally, ethylene and ethane are separated, and the separated pure ethylene and ethane can be further used in industrial production and other applications. However, the current membrane making process is not very mature and cannot meet industrial needs. At least 1 million square meters of membranes that meet actual production needs are required. This is because the membrane has a "tradeoff" effect, that is, there are restrictions on both membrane flux and selectivity.

[0007] CN 103347596A discloses a membrane separation process. A carbon molecular sieve membrane is prepared from a precursor solution of 3,3',4,4'-benzophenonetetracarboxylic dianhydride 5(6)-amino-1-(4'-aminophenyl)-1,3,3-trimethylindan 4,4-bismaleimidodiphenylmethane (BTDA-DAPI), which is then formed into a membrane or hollow fiber, which is pyrolyzed in a vacuum or inert atmosphere to form a carbon molecular sieve membrane. Pyrolysis condition variables include heating rate, thermal cracking time and temperature, which can be used to optimize the separation performance of the membrane.

[0008] Pressure swing adsorption (PSA) can effectively separate mixed gases and is a method that is developing rapidly at present. At the same time, pressure swing adsorption can effectively separate mixed gases and is widely used. That is, under the condition of higher component partial pressure, one or more components in the mixed gas are selectively adsorbed, and desorption is completed by reducing the pressure or vacuuming, and the cycle operation is completed by pressure change. PSA technology is an effective gas separation technology with a wide range of applications. It is suitable for large-volume gas separation and is used to meet the needs of large-scale and extra-large-scale industrial gases. It is also suitable for removing trace impurities and gas purification, especially high-concentration low-boiling impurities that are difficult to remove by other methods. The pressure swing adsorption process has the advantages of room temperature operation, simple process, convenient maintenance, short cycle, large processing capacity, high product gas purity, low energy consumption and high degree of automation. It has become an important separation technology in the field of industrial gas and environmental protection. The adsorbents for separation of C2H4 / C2H6 by pressure swing adsorption mainly include activated carbon materials, metal organic frameworks, zeolite molecular sieves, etc. Activated carbon materials have problems such as small adsorption capacity and large adsorbent consumption, and metal organic frameworks have shortcomings such as weak thermal stability and high production cost. Therefore, these two adsorbents cannot be widely used. Zeolite molecular sieves have attracted widespread attention from scientific researchers due to their good thermal stability, easy pore adjustment, and high selectivity.

[0009] The paper "Novel C-PDA adsorbents with high uptake and preferential adsorption of ethane over ethylene" (Chemical Engineering Science, 2016, Vol. 155, pp. 338-347) reported the preparation of a new porous carbon-based material C-PDA (carbonized polydopamine adsorbent) by a one-step synthesis method, with an adsorption capacity of 7.93 mmol / g for C2H6 and a pore volume of 1.97 cm 3 / g, giving full play to the advantages of activated carbon materials. However, activated carbon adsorption still has certain shortcomings, such as small adsorption capacity, large adsorbent consumption, and decreased adsorption capacity after a period of use.

[0010] The paper “Supramolecular binding and separation of hydrocarbons with in a functionalized porous metal–organic framework” (Nature Chemistry, 2015, Vol. 7, No. 2, pp. 121-129) reported an Al-MOF (NOTT-300). At 293K and 1 bar, its adsorption capacity for C2H4 and C2H6 was 4.28 mmol / g and 0.85 mmol / g, respectively, and its C2H4 / C2H6 selectivity reached 48.7, exceeding the selectivity coefficients of similar MOF materials such as Fe-MOF-74, Co-MOF-74, PAF-1-SO3A, and molecular sieve materials such as NaETS-10 and NaX.

[0011] The paper "Synthesis of Cu-ETS-10 and Study on Adsorption Performance of C2H4 and C2H6" (Journal of Shengli College of China University of Petroleum, 2018, Vol. 32, No. 4, pp. 30-32) reported an ETS-10, Cu 2+ The adsorption capacity of Cu-ETS-10 for C2H4 / C2H6 obtained after ion exchange reached 1.85mmol / g and 0.12mmol / g respectively, and the separation factor reached 14.38.

[0012] The document "Control of zeolite framework flexibility and pore topology for separation of ethane and ethylene" (Science, 2017, Vol. 358, No. 6366, p. 1068) reports a pure silicon molecular sieve with a flexible framework structure and a strong affinity for C2H4. The ITQ-55 molecular sieve opens the pores during the diffusion of C2H4, making the diffusion rate of C2H4 greater than that of C2H6, thereby achieving the separation of C2H4 / C2H6.

[0013] The document "Adsorption properties of ion-exchanged SSZ-13zeolite for ethylene / ethane separation" (Fluid Phase Equilibria, 2021, Vol. 546, p. 113171) reported that an Ag-SSZ-13 molecular sieve exhibited high ethylene and ethane adsorption capacity. Under 303K conditions, the saturated ethylene adsorption capacity of Ag-SSZ-13 was 2.237 mol / kg, and the saturated ethane adsorption capacity was 1.963 mol / kg, but the adsorbent selectivity needs to be improved.

[0014] CN113801337B discloses a metal organic framework material for adsorbing and separating ethylene and ethane, and its preparation method and application. The adsorbent is prepared by a solvothermal method using zinc trifluoroacetate tetrahydrate as a metal salt, terephthalic acid and 3,3',5,5'-tetramethyl-1,1-dihydro-4,4-bipyrazole as organic ligands, and a mixed solvent of N,N-dimethylformamide, methanol and hydrofluoric acid as a solvent. The adsorbent has a good effect of separating ethane / ethylene, but the preparation cost of the adsorbent material is expensive and the use conditions are harsh.

[0015] CN117323959A discloses a separation adsorbent and a method for concentrating ethylene. The adsorbent metal salt active component includes component L1 and component L2, wherein component L1 is selected from Mg 2+ , Ca 2+ and Sr 2+ At least one metal salt of 3+ , Cu 2+ 、Zn 2+ and Mn 2+ The adsorbent has improved ethylene adsorption capacity and adsorption selectivity, but the metal salt used in the adsorbent is expensive because its metal cation exchange capacity is relatively large. Summary of the invention

[0016] In view of this, the present invention provides a molecular sieve for adsorbing and separating ethylene and ethane, and a preparation method and a use method thereof, which can effectively improve the adsorption selectivity of ethylene compared with existing molecular sieves to solve the above-mentioned technical problems existing in the prior art.

[0017] In order to achieve the above object, one of the technical solutions of the present invention is:

[0018] A molecular sieve for adsorbing and separating ethylene and ethane is an Ag-Na-LTA molecular sieve or Na-LTA with synergistic effect of Ag-Na dual ions.

[0019] Another technical solution of the present invention is a method for preparing the above molecular sieve, and the method for preparing Na-LTA molecular sieve comprises the following steps:

[0020] calcining the Na-LTA molecular sieve to obtain Na-LTA;

[0021] The preparation method of Ag-Na-LTA molecular sieve comprises the following steps:

[0022] The silver salt and the Na-LTA molecular sieve are ion exchanged and then calcined to obtain Ag-Na-LTA.

[0023] On the basis of the above technical solution, the present invention further defines the solution as follows:

[0024] Further, the mass ratio of silver salt to Na-LTA is 0-0.34:1;

[0025] Furthermore, the silver salt is silver nitrate;

[0026] Na-LTA molecular sieve pH≤11, bulk density 0.70-0.75g / cm 3 , Si / Al=1, static water adsorption ≥27%, particle size 7.5-9.5μm.

[0027] Further, the exchange concentration of silver ions is 0-0.5 mol / L;

[0028] The temperature of ion exchange is 273~363K, and the time is 1~5h.

[0029] Furthermore, the calcination treatment temperature is 473-873 K, the time is 3-7 h, and the heating rate is 1.8-3.0 K / min.

[0030] Furthermore, the method also includes a drying operation before calcining the exchange product, wherein the drying temperature is 333 to 383 K and the time is 10 to 24 hours.

[0031] Another technical solution of the present invention is a method for using the above molecular sieve, comprising:

[0032] The molecular sieve is degassed at a temperature of 387 to 873 K for 1 to 6 hours and then placed in an adsorption tower for separation of ethylene and ethane.

[0033] Furthermore, the adsorption temperature is 273-323 K, the adsorption equilibrium time is 90-1800 s, and the adsorption pressure is 0-110 kPa;

[0034] The number of the adsorption tower is at least one.

[0035] The beneficial effects of the present invention are:

[0036] The molecular sieve for adsorptive separation of C2H4 / C2H6 of the present invention is a molecular sieve with LTA configuration, which not only provides a new adsorption material for adsorptive separation of C2H4 / C2H6, thereby adding a new optional approach to the adsorptive separation technology of C2H4 / C2H6, but also has a better working adsorption capacity for ethylene than the existing molecular sieves with LTA configuration. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is the X-ray diffraction XRD spectrum of the Na-LTA molecular sieve of Example 1 of the present invention;

[0038] Figure 2 This is a scanning electron microscope (SEM) spectrum of the Na-LTA molecular sieve of Example 1 of the present invention;

[0039] Figure 3 yes Figure 2 Multiple magnification of the image;

[0040] Figure 4 The adsorption isotherm curve of ethylene and ethane at 298K of the Ag-Na-LTA molecular sieve of Example 2-3 of the present invention;

[0041] Figure 5 The adsorption isotherms of ethylene at 298K for Ag-K-LTA, Ag-Ca-LTA, K-LTA, Na-LTA and Ca-LTA molecular sieves in the comparative examples of the present invention;

[0042] Figure 6 These are the adsorption isotherms of ethane adsorbed at 298K by Ag-K-LTA, Ag-Ca-LTA, K-LTA, Na-LTA and Ca-LTA molecular sieves in the comparative examples of the present invention. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] Characterization of Na-LTA

[0046] The commercially available Na-LTA samples were analyzed by XRD and SEM. The results were as follows: Figure 1-3 As shown, Figure 1 It can be seen that the sample has the following characteristic peaks:

[0047] There is a diffraction peak in the range of 7-8 at 2θ (200 crystal plane);

[0048] There is a diffraction peak in the range of 10-11 at 2θ (220 crystal plane);

[0049] There is a diffraction peak in the range of 12-13 at 2θ (222 crystal plane);

[0050] There is a diffraction peak in the range of 16-17 at 2θ (420 crystal plane);

[0051] There is a diffraction peak in the range of 22-23 at 2θ (620 crystal plane);

[0052] There is a diffraction peak in the range of 23-24 at 2θ (622 crystal plane);

[0053] There is a diffraction peak in the range of 26-27 at 2θ (640 crystal plane);

[0054] There is a diffraction peak in the range of 29-30 at 2θ (820 crystal plane);

[0055] There is a diffraction peak in the range of 33-34 2θ (664 crystal plane).

[0056] The purchased Na-LTA has LTA molecular sieve configuration (PDF#43-0142) and high crystallinity. SEM characterization shows that the particles are evenly distributed and the particle size is about 2-5 μm. It can also be seen that the sample has high crystallinity and less amorphous.

[0057] Example 2

[0058] Preparation of Ag-Na-LTA Molecular Sieve

[0059] 2 g of the Na-LTA molecular sieve purchased in Example 1 was mixed with 40 ml of 0.05 M and 0.1 M silver nitrate solutions in a round-bottom flask, respectively. A magnetic stirrer was then placed, a condenser was installed, and ion exchange was performed in a water bath at 353 K for 2 h to obtain a filter cake.

[0060] The filter cake after filtration and rinsing was placed in a drying oven at 373K for 24 hours. The dried molecular sieve was calcined in a muffle furnace, heated to 673K ​​at a heating rate of 3K / min, and maintained at 673K ​​for 4 hours to obtain 0.05M Ag-Na-LTA and 0.1M Ag-Na-LTA after ion exchange, respectively.

[0061] Different Ag + The calculation results of Si / Al and ion exchange degree of concentration-exchanged Na-LTA are summarized in Table 1.

[0062] Table 1 Different Ag +Ion concentration LTA molecular sieve silicon aluminum ratio, silver aluminum ratio and sodium aluminum ratio (atomic percentage)

[0063] Sample name Ion exchange fluid concentration Si / Al Ag / Al Na / Al Na-LTA —— 1.00 —— 1.00 0.05M-Ag-Na-LTA 0.05mol / L 1.00 0.03 0.97 0.1M-Ag-Na-LTA 0.1mol / L 1.00 0.05 0.95

[0064] The Ag content of the above samples is relatively low, among which the Ag content of 0.05M-Ag-Na-LTA is 2.01%, and the Ag content of 0.1M-Ag-Na-LTA is 3.99% (the above proportions are all mass percentages).

[0065] Example 3

[0066] Adsorption and separation performance of Ag-Na-LTA molecular sieve for C2H4 / C2H6

[0067] The different Ag in Example 2 are respectively + Concentration-exchanged Ag-Na-LTA was used for the separation of C2H4 / C2H6, and the adsorption isotherm was measured by a low-pressure physical adsorption analyzer. About 0.5 g of Ag-Na-LTA was weighed. In order to avoid the influence of water molecules in the molecular sieve on the adsorption effect, the test position was degassed at 523 K for 2 h to activate the sample. The adsorption temperature was maintained at 298 K in a constant temperature water bath. The adsorption equilibrium times of C2H4 and C2H6 on the molecular sieve were 90 s and 90 s, respectively.

[0068] An important factor in PSA separation is the change in the adsorption of the two components during the pressure change cycle. The adsorption capacity of an adsorbent refers mainly to the difference between the adsorption of the more easily adsorbed component at high pressure and the desorption at low pressure. In short, the adsorption capacity depends on the adsorption under mixed conditions (i.e., using a binary isotherm).

[0069] However, the adsorption isotherms of the pure components are sufficient for the calculation of the parameters. Comparison of the adsorption capacities of the two components is an ideal method for determining the adsorption performance of a particular PSA cycle. The better the adsorbent, the higher the value of the selectivity parameter (S).

[0070] Generally, in industrial PSA separation, the adsorption process pressure is 50-100 kPa, while the desorption pressure is only 10 kPa. Therefore, in this paper, the working capacity is defined as the difference between the gas adsorption capacity at 100 kPa and 0.06 kPa according to the industrial separation requirements.

[0071] The adsorption isotherm curve was fitted by the Langmuir adsorption model, such as Figure 4 The Henry constant (k) and equilibrium selectivity (α) were used to calculate the adsorption isotherm curves of different Ag. +The C2H4 / C2H6 adsorbent selectivity parameters (S) of the concentration-exchanged Ag-Na-LTA molecular sieve are shown in Table 2.

[0072] Table 2 Different Ag + Adsorption performance data of C2H4 and C2H6 by Ag-Na-LTA with concentration exchange

[0073]

[0074] Note: 1. Adsorbent selectivity parameter (S):

[0075]

[0076] 2.C2H4 working capacity Δq:

[0077]

[0078] From Table 2 and Figure 4 It can be seen that in different Ag + Among the concentration-exchanged Ag-Na-LTA, the saturated adsorption capacity of 0.1M Ag-Na-LTA for C2H4 is the highest in the entire pressure range, reaching 2.48mmol / g, while the saturated adsorption capacity for C2H6 is only 0.02mmol / g. In addition, the working capacity of 0.1M Ag-Na-LTA for C2H4 is greater than that of 0.05M Ag-Na-LTA. Due to its lower ethane working capacity, the adsorbent selectivity parameter (S) is still the highest among all samples, reaching 1215610. Therefore, under different Ag concentrations, the adsorption capacity of 0.1M Ag-Na-LTA for C2H4 is higher than that of 0.05M Ag-Na-LTA. + Among the concentration-exchanged Ag-Na-LTA, 0.1 M Ag-Na-LTA is most suitable for PSA separation of ethylene and ethane.

[0079] Comparative Example

[0080] The separation of C2H4 / C2H6 by different existing adsorption materials and Ag-Na-LTA synthesized in Example 2 was compared.

[0081] 1. Preparation of Ag-K-LTA molecular sieve

[0082] K-LTA molecular sieve is commercially available, pH ≤ 10.8, bulk density 0.66-0.79 g / cm 3 , Si / Al=1, K + Exchange degree ≥45%, static water adsorption ≥25.5%, particle size 7.5-9.5μm.

[0083] 2 g of the purchased K-LTA molecular sieve was mixed with 40 ml of 0.1 M silver nitrate solution in a round-bottom flask, and then a magnetic stirrer was placed, a condenser was installed, and ion exchange was performed in a water bath at 353 K for 2 h to obtain a filter cake.

[0084] The filter cake after filtration and washing was placed in a drying oven at 373K for 24 hours. The dried molecular sieve was calcined in a muffle furnace, heated to 773K at a heating rate of 3K / min, and maintained at 773K for 4 hours to obtain 0.1M Ag-K-LTA after ion exchange.

[0085] 2. Preparation of Ag-Ca-LTA molecular sieve

[0086] Ca-LTA molecular sieve is commercially available, pH ≤ 10.5, bulk density 0.71-0.77 g / cm 3 , Si / Al=1, Ca 2+ Exchange degree ≥75%, static water adsorption ≥27.5%, particle size 7.5-9.5μm.

[0087] 2 g of the purchased Ca-LTA molecular sieve was mixed with 40 ml of 0.1 M silver nitrate solution in a round-bottom flask, and then a magnetic stirrer was placed, a condenser was installed, and ion exchange was performed in a water bath at 353 K for 2 h to obtain a filter cake.

[0088] The filter cake after filtration and washing was placed in a drying oven at 373K for 24 hours. The dried molecular sieve was calcined in a muffle furnace, heated to 773K at a heating rate of 3K / min, and maintained at 773K for 4 hours to obtain 0.1M Ag-K-LTA after ion exchange.

[0089] Table 3 Different Ag + Ion concentration LTA molecular sieve silicon aluminum ratio, silver aluminum ratio, sodium aluminum ratio, potassium aluminum ratio and calcium aluminum ratio ()

[0090] Sample name Ion exchange fluid concentration Si / Al Ag / Al Na / Al K / Al Ca / Al K-LTA —— 1.00 —— 0.45 0.55 —— 0.1M-Ag-K-LTA 0.1mol / L 1.00 0.06 0.62 0.32 —— Ca-LTA —— 1.00 —— 0.55 —— 0.45 0.1M-Ag-Ca-LTA 0.1mol / L 1.00 0.04 0.52 —— 0.44

[0091] The Ag content of the above samples is relatively low, among which the Ag content of 0.1M-Ag-K-LTA is 4.59%, and the Ag content of 0.1M-Ag-Ca-LTA is 4.21% (the above proportions are all mass percentages).

[0092] The 0.1Ag-K-LTA molecular sieve, 0.1Ag-Ca-LTA molecular sieve, Na-LTA molecular sieve and Ca-LTA molecular sieve were respectively subjected to the experiment on the pressure swing adsorption of ethylene and ethane in Example 3. The adsorption performance data results are shown in Table 2 and Figure Na-LTA, Figure 6 .

[0093] Table 4 Adsorption performance data of different adsorbents for C2H4 and C2H6

[0094]

[0095] Table 4 and Figure 5 , Figure 6 The results show that the adsorption performance of 0.1M Ag-Na-LTA molecular sieve and K-LTA, Na-LTA, Ca-LTA, 0.1M-Ag-K-LTA and 0.1M-Ag-Ca-LTA for C2H4 / C2H6 is compared.

[0096] Ca-LTA molecular sieve, which is often used as an adsorbent, has a low saturated adsorption capacity for C2H4 on the one hand, and a high saturated adsorption capacity for C2H6 on the other hand. Therefore, its adsorbent selectivity parameter (S) is low, only 7.57; the saturated adsorption capacity of adsorbent ethylene of Na-LTA is small, and the high selectivity parameter has no practical significance.

[0097] Comparing the LTA molecular sieves that are also exchanged with Ag, 0.1M-Ag-K-LTA and 0.1M-Ag-Ca-LTA, the saturated adsorption capacity of 0.1M-Ag-K-LTA for C2H4 and C2H6 is very small, resulting in a small adsorbent selectivity parameter. The adsorption of ethylene and ethane by K-LTA without Ag exchange is small, and the adsorption of ethylene and ethane is close, resulting in an adsorbent selectivity parameter of 0.99. The saturated adsorption capacity of 0.1M-Ag-Ca-LTA for C2H4 and C2H6 is large. Although its adsorbent selectivity parameter reaches 26.01, it still cannot separate C2H4 / C2H6 well. This shows that in LTA molecular sieves, K + and Ca 2+ The increase in ions affects the Na + and Ag + The synergistic effect between them cannot control the Ag content and improve the adsorbent selectivity of C2H4 / C2H6.

[0098] A comprehensive comparison of K-LTA, Na-LTA, Ca-LTA, 0.1M-Ag-K-LTA and 0.1M-Ag-Ca-LTA shows that the Ag-Na-LTA of the embodiment of the present invention effectively suppresses the saturated adsorption capacity of ethane, has a higher adsorbent selectivity parameter, and achieves the purpose of adsorption and separation of C2H4 / C2H6.

[0099] The Ag-Na-LTA molecular sieve of the present invention is more suitable for vacuum pressure swing adsorption to separate C2H4 and C2H6 with high selectivity.

Claims

1. A molecular sieve for adsorption separation of ethylene and ethane, characterized in that: The molecular sieve is Na-LTA or Ag-Na-LTA molecular sieve.

2. A method for preparing a molecular sieve for adsorption separation of ethylene and ethane, characterized in that: The preparation method of Na-LTA molecular sieve comprises the following steps: calcining the Na-LTA molecular sieve to obtain Na-LTA; The preparation method of Ag-Na-LTA molecular sieve comprises the following steps: The silver salt and the Na-LTA molecular sieve are ion exchanged and then calcined to obtain Ag-Na-LTA.

3. The preparation method according to claim 2, characterized in that: The mass ratio of silver salt to Na-LTA is 0-0.34:

1.

4. The preparation method according to claim 2 or 3, characterized in that: The silver salt is silver nitrate; The Na-LTA molecular sieve has a pH value of ≤11 and a bulk density of 0.70-0.75 g / cm 3 , Si / Al=1, static water adsorption ≥27%, particle size 7.5-9.5μm.

5. The preparation method according to claim 2, characterized in that: The exchange concentration of silver ions is 0-0.5 mol / L; The temperature of ion exchange is 273~363K, and the time is 1~5h.

6. The preparation method according to claim 2, characterized in that: The calcination temperature is 473-873 K, the calcination time is 3-7 h, and the heating rate is 1.8-3.0 K / min.

7. The preparation method according to claim 2, characterized in that: The process also includes a drying process before calcining the exchange product. The drying process is performed at a temperature of 333 to 383 K and for a time of 10 to 24 hours.

8. A method for using the molecular sieve for separation of ethylene and ethane by adsorptive separation according to claim 1 and / or the molecular sieve for separation of ethylene and ethane by adsorptive separation obtained by the preparation method according to any one of claims 2 to 7, characterized in that: include: The molecular sieve is degassed at a temperature of 387 to 873 K for 1 to 6 hours and then placed in an adsorption tower for separation of ethylene and ethane.

9. The method of use according to claim 8, characterized in that: The adsorption temperature is 273-323 K, the adsorption equilibrium time is 90-1800 s, and the adsorption pressure is 0-110 kPa; The number of the adsorption tower is at least one.

Citation Information

Patent Citations

  • Polyimide-based carbon molecular sieve membrane for ethylene / ethane separations

    CN103347596A

  • A metal-organic framework material for the adsorption and separation of ethylene ethane, its preparation method and application

    CN113801337B

  • Separation adsorbent and method for concentrating ethylene

    CN117323959A

  • Distillation trays

    US20220331709A1

Cited By

  • Molecular sieve for adsorbing and separating ethylene and ethane as well as preparation and use methods of molecular sieve

    CN121103308A